Educating for Values-Driven Leadership - Gentile, Mary C (Business Expert Press, 2013)
Ebook from IG Library ; Despite four decades of good faith effort to teach ethics in business schools, you'll still find today headlines about egregious excess and scandal. It becomes reasonable to ask why these efforts have not been working. Business faculty in ethics courses spend a lot of time teaching theories of ethical reasoning and analyzing those big, thorny dilemmas--triggering what one professor called 'ethics fatigue.' But what if faculty stopped focusing on ethical analysis and focused on a new curriculum--one that builds a conversation across the core curriculum (not only in ethics courses) and also provides the teaching aids for a new way of thinking about ethics education? This is where Giving Voice to Values (GVV) comes in--the GVV curriculum asks the question: 'What if I were going to act on my values? What would I say and do? How could I be most effective?'